The role of business ethics in establishing principles of corporate governance (Numerus academy review, 2026)
Through this research paper, we can say that the recent global financial crises resulting from corruption and mismanagement have exacerbated the crises of major internationalcompanies, which resulted in losses of billions of dollars and led to a rise in the bill ofcorruption, and became a burden on companies and the global economy as a whole.Where all these circumstances helped to search for principles and tools that ensure theproper conduct of all the activities of the institution, and help to reduce risks, improve performance and opportunities for development of markets and increase competitiveness,and search for rules that increase the confidence of the investor public and achieve the objectives of stakeholdersAnd among the most important of these tools that achieve goodgovernance for these institutions, we find that the external audit, which is concerned with setting its standards, rules and ethics, is private bodies and international organizations that are making tangible efforts to control the practice of the profession.